2015
DOI: 10.1007/s12262-015-1362-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Chronic Pancreatitis

Abstract: Advances over the past decade have indicated that a complex interplay between environmental factors, genetic predisposition, alcohol abuse, and smoking lead towards the development of chronic pancreatitis. Chronic pancreatitis is a complex disorder that causes significant and chronic incapacity in patients and a substantial burden on the society. Major advances have been made in the etiology and pathogenesis of this disease and the role of genetic predisposition is increasingly coming to the fore. Advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 97 publications
1
28
0
1
Order By: Relevance
“…Uroflowmetry is used as a diagnostic test to assess the function of the urinary tract. Stool analysis is also important for diagnosing gastrointestinal disorders, including poor nutrient absorption 27 , pancreatitis [28][29][30][31][32][33] , infections [34][35][36] and cancers 17,37,38 . In particular, the Bristol stool form scale (BSFS; BS1-BS7) categorizes the form of stool to be used as an assessment tool for the diagnosis of various bowel diseases or evaluation of treatment efficacy (Supplementary Table 1).…”
mentioning
confidence: 99%
“…Uroflowmetry is used as a diagnostic test to assess the function of the urinary tract. Stool analysis is also important for diagnosing gastrointestinal disorders, including poor nutrient absorption 27 , pancreatitis [28][29][30][31][32][33] , infections [34][35][36] and cancers 17,37,38 . In particular, the Bristol stool form scale (BSFS; BS1-BS7) categorizes the form of stool to be used as an assessment tool for the diagnosis of various bowel diseases or evaluation of treatment efficacy (Supplementary Table 1).…”
mentioning
confidence: 99%
“…Regarding the evaluation of outcomes, visual analogue pain scale was used for pain control evaluation. The 12-Item Short-Form General Health Survey (SF-12) questionnaire was used for quality of life assessment (7). Dosage of serum glycated hemoglobin, peptide-C and measure of fat fecal content by Sudanstain test were used to assess endocrine and exocrine pancreatic function.…”
Section: Methodsmentioning
confidence: 99%
“…The Frey procedure consists of excising the anterior head of the pancreas, including the major and minor pancreatic ducts and the duct of Santorini, with preservation of the posterior pancreatic head and the pancreatic neck [51]. Additionally, the main pancreatic duct is opened, and a Roux-en-Y limb is brought up to complete a pancreaticojejunostomy [51]. Studies have shown that post-operative morbidity in the Frey procedure ranges from 7.5% to 39%, with mortality rates ranging from 0% and 2.4% [51,[54][55][56].…”
Section: Surgical Management Of Chronic Pancreatitismentioning
confidence: 99%